2006
DOI: 10.1556/abiol.57.2006.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of morphine-induced alterations in rat submandibular gland function by N-methyl-D-aspartate agonist

Abstract: The effects of morphine, 1-aminocyclobutane-cis-1,3-dicarboxylic (ACBD; NMDA agonist) and 3-((R)2-carboxypiperazin-4-yl)-propyl-l-phosphoric acid (CPP; NMDA antagonist) and their concurrent therapy on rat submandibular secretory function were studied. Pure submandibular saliva was collected intraorally by micro polyethylene cannula from anaesthetized rats using pilocarpine as secretagogue. Intraperitoneal injection of morphine (6 mg/kg) induced significant inhibition of salivary flow rate, total protein, calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…One type aimed to treat AD, such as acetylcholine receptor inhibitors and N ‐methyl‐ d ‐aspartic acid receptor antagonists; the other type was selected to treat manic disorder, insomnia and other mental problems, such as symptomatic therapy dopamine receptor blockers, 5‐HT receptor blockers, and GABA receptor agonists. These drugs could induce xerostomia with oligoptyalism (Hashemi et al, 2006; Yamamura & Nonaka, 2019), which might affect the oral microbiomes. Regarding the side effects, patients spent more than 5 min to dribble 2.0 ml of saliva, and it was difficult for them to cooperate, explaining why we selected stimulated saliva instead of unstimulated saliva.…”
Section: Discussionmentioning
confidence: 99%
“…One type aimed to treat AD, such as acetylcholine receptor inhibitors and N ‐methyl‐ d ‐aspartic acid receptor antagonists; the other type was selected to treat manic disorder, insomnia and other mental problems, such as symptomatic therapy dopamine receptor blockers, 5‐HT receptor blockers, and GABA receptor agonists. These drugs could induce xerostomia with oligoptyalism (Hashemi et al, 2006; Yamamura & Nonaka, 2019), which might affect the oral microbiomes. Regarding the side effects, patients spent more than 5 min to dribble 2.0 ml of saliva, and it was difficult for them to cooperate, explaining why we selected stimulated saliva instead of unstimulated saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have used salivary gland as models to conduct research where drugs were used; however, these studies were typically physiologically based with little to no focus on drug pharmacokinetics and pharmacodynamics. [13][14][15] In a study of rats acutely treated with morphine, morphine was found in several internal organs, including the submandibular salivary gland. 16 The facial and lingual arteries branch from the external carotid artery and supply blood to facial skin, facial muscles, submandibular salivary gland, and various tissue in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Given its anatomical location, ease of excision, and the amount of tissue typically available, the submandibular salivary gland was a convenient solid tissue to evaluate. Animal studies have used salivary gland as models to conduct research where drugs were used; however, these studies were typically physiologically based with little to no focus on drug pharmacokinetics and pharmacodynamics 13–15 . In a study of rats acutely treated with morphine, morphine was found in several internal organs, including the submandibular salivary gland 16…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that morphine increase lactate levels in serum, however its effects on salivary lactate concentration are unknown [13]. In humans and rats, the morphine administration was correlated to hyposalivation, and associated with changes in the ionic composition [14][15]. Bearing in mind that amylase is the most abundant protein in saliva [16], salivary amylase concentration decreased after morphine treatment [17].…”
Section: Introductionmentioning
confidence: 99%